2010
DOI: 10.1093/gerona/glq052
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Musculoskeletal Pain to Postural Balance in Community-Dwelling People Aged 75 Years and Older

Abstract: The findings demonstrate a direct relationship between the moderate to severe musculoskeletal pain and impaired postural balance. Pain seems to be an important target for the prevention of balance impairment and further mobility limitation among older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 40 publications
7
66
1
2
Order By: Relevance
“…Mental stress causes neuromuscular tension and correlates with musculoskeletal complaints, such as pain (Kopec and Sayre 2004). In crosssectional studies, perceived pain was found to be associated with poorer physical functioning (Lihavainen et al 2010), and perceived pain also predicts subsequent disabilities (Hughes et al 1994). Stress is also associated with cardiovascular risk factors, such as higher smoking rates and metabolic indicators including higher blood cholesterol and glucose levels (Vrijkotte et al 1999), and thus consequently with incident cardiovascular disease (Greenwood et al 1996) and diabetes (Nyberg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mental stress causes neuromuscular tension and correlates with musculoskeletal complaints, such as pain (Kopec and Sayre 2004). In crosssectional studies, perceived pain was found to be associated with poorer physical functioning (Lihavainen et al 2010), and perceived pain also predicts subsequent disabilities (Hughes et al 1994). Stress is also associated with cardiovascular risk factors, such as higher smoking rates and metabolic indicators including higher blood cholesterol and glucose levels (Vrijkotte et al 1999), and thus consequently with incident cardiovascular disease (Greenwood et al 1996) and diabetes (Nyberg et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed review of full texts led to excluding 13 studies due to assessment of sway during single-leg stance [15][16][17] or quiet stance with shoulder flexion [18], the lack of a control group [19][20][21], use of a dynamic platform for assessment of postural sway [22] or external perturbations [23,24]. Furthermore, studies were excluded from the review due to use of COP parameters not reflecting sway amplitude or velocity [25], and including individuals with general musculoskeletal pain [26] or experimentally induced Correction for confounding effect on dependent variables Positive points were assigned if confounders (i.e. age, gender, body height, body mass and physical activity) were taken into account, or appropriate matching on these variables was performed.…”
Section: Literature Searchmentioning
confidence: 99%
“…[20][21][22] An experimental report also stipulates that prolonged exposure to nociceptive stimulations from the skin or sore muscles could lead to over estimation of the level of torque generated in the painful limb of an individual thereby compromising the balance.…”
Section: Discussionmentioning
confidence: 99%